Patriarchy and Women Abuse: Perspectives from Ancient Israel and Africa - Ademiluka, Solomon Olusola (Old Testament Essays, 2018)
It is often claimed that women abuse inevitably emanates from patriarchy. Using ancient Israel and Africa as contexts, this article assesses the correlation between patriarchy and violence against women. The article suggests in these contexts, it is not all men are who are perpetrators of women abuse; rather, there is evidence of female perpetrators of sexual violence against men; and that in the ancient and modern societies, there is also homosexual violence. Rather than patriarchy, the major cause of women abuse is a personality disorder characterised, among other traits, by aggression against women, alcoholism and drug abuse – the latter two traits are often responsible for women abuse. Being accustomed to domestic violence from youth and low socio-economic status are also causes of women abuse.